Review of Marine Pipe Repair Methods in Indonesia - Juswan Sade (Collaborate, 2023)
Marine pipes are subject to risks that can cause damage to them. These risks include internal corrosion due to corrosive fluids, erosion caused by solid particles in the flowing fluid, external corrosion, and impact by anchors to the pipe's external surface. If damage and leakage occur in the pipeline, in addition to considerable losses in products and significant economic losses, it also causes environmental pollution. Therefore, identifying marine pipe repair methods and knowing the conditions under which each can be applied is essential. From the first days of using marine pipes until now, many methods have been used to repair pipe defects. While all defects remain the same, repair methods continue to improve to reduce time costs and increase safety and operational certainty. The impact levels vary according to damage type, working environment (land and sea), working pressure and temperature, pipe length, fluid, etc. Considering all this and the fact that kilometres of marine pipes exist, It is essential to know and master the various pipe repair methods and master them. Therefore, according to the parameters and methods mentioned in this article, various types of marine pipe repair and necessary equipment have been reviewed.